The influence of service quality and passenger satisfaction towards electric train services (ETS): A PLS-SEM approach - Azmi Mat; Norliza Saiful Bahry; Nur Liana Kori; Zarina Abdul Munir; Norzaidi Mohd Daud (Foundations of Management, 2019)
This research is about service quality (responsiveness, reliability, tangible, safety and securi-ty) dimensions becoming major determinants of passenger satisfaction towards Electric Train Services (ETS). The significance of this study is intended to assist Keretapi Tanah Melayu Berhad (KTMB) to establish the service offered and to identify the important aspects of service quality that affect pas-senger satisfaction. A total of 280 questionnaires were distributed to ETS passengers, who were using the service from Kuala Lumpur Sentral Station to Padang Besar Station. The main objective of this study was to investigate the relationship between service quality dimensions and passenger satisfaction towards ETS. Data gathered were analyzed using partial least square (PLS) method. The study con-cluded that service quality dimensions are the factors affecting the passenger satisfaction towards ETS. In addition, service quality can also define the significant relationship between passenger satisfaction towards ETS. Other than that, several useful recommendations were made regarding the findings of this study.
Keywords: L90; L91; L92; M10; N75; 650; passenger satisfaction; service quality; electric train services (ETS)